Extracellular Vesicles in Tumors: A Potential Mediator of Bone Metastasis - Li, Shenglong; Wang, Wei (Frontiers in Cell and Developmental Biology, 2021)
As one of the most common metastatic sites for malignant tumors, bone has unique microenvironment for the growth and prosperity of metastatic tumor cells. Bone metastasis is a common complication in tumor patients of which the incidence accounts for 15%~20% of systemic metastasis, only secondary to that of lung and liver metastasis. Malignant tumors vulnerable to bone metastasis include lung cancer, breast cancer and prostatic cancer. Exosome is a lipid membranous vesicle released from different types of cells. It is clear that exosomes are associated with multiple biological phenomena, including the development of cancer, and are crucial in the intracellular communication via transporting intracellular substances. Recent studies have shown that tumor exosomes implicate in the development of cancers. However, the potential roles of exosomes in the pathological exchange of bone cells between tumors and bone microenvironment remain an emerging area. This review focused on the roles of tumor-derived exosomes in bone metastasis and possible regulatory mechanism.